Pengaruh Kejelasan Sasaran Anggaran, Kompetensi Aparat Dan Kepemimpinan Terhadap Akuntabilitas Dengan Whistleblowing Sebagai Pemoderasi Di Salapian - Nurfiza, Marta; Simanjuntak, Arthur; Situmorang, Duma Rahel (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to determine the effect of Budget Goal Clarity, Village Apparatus Competence, and Village Government Leadership on Village Fund Management Accountability. In addition, this study also aims to test whether the Whistleblowing variable moderates the relationship between Budget Goal Clarity, Village Apparatus Competence, and Village Government Leadership on Village Fund Management Accountability in Villages in Salapian District, Langkat Regency. This study uses quantitative methods, the sample collection technique in this study is to use a questionnaire, the population and sample in this study were village officials in Salapian District, Langkat Regency many as 80 village officials with sampling techniques, namely probability sampling. The data were analyzed using the Moderated regression analysis method with interaction tests. The results of the partial test hypothesis show that budget target clarity affects the accountability of village fund management, the competence of village officials affects the accountability of village fund management and village government leadership affects the accountability of village fund management. The results of the simultaneous test hypothesis show that the clarity of budget targets, the competence of village officials, and village government leadership, have a positive and significant effect on the accountability of village fund management. MRA analysis shows that whistleblowing is able to moderate the competence of village officials on the accountability of village fund management, while whistleblowing is not able to moderate the clarity of budget targets and village government leadership on the accountability of village fund management.